Bio-fabrication of pigment-capped silver nanoparticles encountering antibiotic-resistant strains and their cytotoxic effect towards human epidermoid larynx carcinoma (HEp-2) cells. Issue 28 (21st May 2019) - Muthukrishnan, Lakshmipathy; Chellappa, Muralidharan; Nanda, Anima; Thukkaram, Sudhakar; Selvaraj, Gracyfathima; Muthiah, Bavanilatha; Sagadevan, Suresh; Lett, J. Anita
Abstract : Bacterial biomolecule-mediated nanoparticle (NP) synthesis constitutes a reliable, eco-friendly approach that ameliorates green-chemistry principles. Abstract : Bacterial biomolecule-mediated nanoparticle (NP) synthesis constitutes a reliable, eco-friendly approach that ameliorates green-chemistry principles. In this study, stable silver nanoparticles were synthesized by exposing aqueous silver ions to an extracellular diffusible pigment produced by Pseudomonas aeruginosa (PA6) under optimized laboratory conditions. Spectroscopic and microscopic analyses showed the typical characteristics of silver with an average size of ∼28.30 nm and spherical shape. The particles were polydispersed and showed no definite agglomeration with a zeta potential of −32.3 mV, conferring stability. Antimicrobial studies were carried out using 5, 15, 25 and 50 μg mL −1 concentrations of pcAgNPs, which showed significant antibacterial activity toward clinically important pathogens at all concentrations compared to with the control sample. The bactericidal effect induced by pcAgNPs associated with cell damage was well demonstrated using electron microscopic studies. ROS production was measured using the DCFH-DA method and the oxidative stress was assessed by measuring the reduced glutathione (GSH) levels. Cytotoxicity studies on HEp-2 (Human Epidermoid Larynx Carcinoma) cells exposed to pcAgNPs showed dose-dependent cytotoxic effect with IC50 of 14.8 μg mL −1 compared to with IC50 of 7.38 μg mL −1 for the Vero cell control. Mechanistically, the pcAgNPs activated p53 that induced catalase, leading to apoptosis and DNA fragmentation via a p53 transcriptional pathway and electron transport arrest, which resulted in cell death. This synergistic efficacy of pigment-AgNPs demonstrated excellent antimicrobial and anti-proliferative activities, providing a potential lead for developing a broad-spectrum antibacterial agent and improving the therapeutic modalities targeting carcinoma cells at the gene level.